Quality control of a medicinal larval (Lucilia sericata) debridement device based on released gelatinase activity - Pickles, S.F.; Pritchard, David I. (Wiley, 2017)
Lucilia sericata Meigen (Diptera: Calliphoridae) larvae are manufactured worldwide for the treatment of chronic wounds. Published research has confirmed that the primary clinical effect of the product, debridement (the degradation of non-viable wound tissue), is accomplished by a range of enzymes released by the larvae during feeding. The quality assessment of larval activity is currently achieved during production using meat-based assays, which monitor insect growth and/or the reduction in substrate mass. To support this, we have developed a complementary radial-diffusion enzymatic assay (RDEA) to produce a visual and measureable indication of the activity of larval alimentary products (LAP) collected under standardised conditions, against a gelatin substrate. Using basic laboratory equipment and reagents, the assay is rapid and suited to high-throughput. Assay reproducibility is high (SD 0.06 - 0.27, CV 0.75 - 4.31%) and the LAP collection procedure does not adversely affect larval survival (mortality < 2%). As a cost- and time-effective method, it is suited to academic or industrial use, supporting good manufacturing (or laboratory) practice (GMP and GLP) as a quality control (QC) assay.